2013
DOI: 10.5539/ijef.v5n3p49
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Bank Share Prices and Their Impact on National Stock Market Indices: Comparing Countries at Different Levels of Economic Development during Recessionary and Non-Recessionary Periods

Abstract: The performance of banks and their effects on the global economy has been of interest to politicians, academicians, businesses and the general public especially in connection with the 2008/09 credit crisis. In particular, the extent to which the bank stock prices affected the national stock market indices in different countries before and during the crisis is unclear. It is also not clear whether the national stock markets of countries at different levels of economic development reacted differently to the cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
6
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 33 publications
9
6
1
Order By: Relevance
“…FTSE 100 started at around 8900 points, reduced slightly, and then increased gradually to around 10300 points while NSE 20 Share index started at around 3000 points in April 2006 , reduced slightly and rose gradually to around 4100 points in July 2007. This agrees with the observations made by Komo & Ngugi (2013) who agreed that NSE is highly interlinked with the UK stock market despite NSE being an emerging market and also geographically very far from the European Country. Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…FTSE 100 started at around 8900 points, reduced slightly, and then increased gradually to around 10300 points while NSE 20 Share index started at around 3000 points in April 2006 , reduced slightly and rose gradually to around 4100 points in July 2007. This agrees with the observations made by Komo & Ngugi (2013) who agreed that NSE is highly interlinked with the UK stock market despite NSE being an emerging market and also geographically very far from the European Country. Fig.…”
Section: Resultssupporting
confidence: 92%
“…The findings indicated that all indices were affected by global financial crisis. According to Komo and Ngugi (2013), these findings showed a convergence between the results and existing theories that security market indicators react negatively to news of a failing global market. In the findings, a suprise observation was that the security market indices of Kenya (NSE 20 Share Index) and UK (FTSE 100) had the second highest correlation-that is following the highest correlation coefficient which was between FTSE and NYSE.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations